Exposure to air pollution and meteorological factors associated with children's primary care visits at night due to asthma attack: case-crossover design for 3-year pooled patients. Issue 4 (3rd May 2015) - Yamazaki, Shin; Shima, Masayuki; Yoda, Yoshiko; Oka, Katsumi; Kurosaka, Fumitake; Shimizu, Shigeta; Takahashi, Hironobu; Nakatani, Yuji; Nishikawa, Jittoku; Fujiwara, Katsuhiko; Mizumori, Yasuyuki; Mogami, Akira; et al.
Abstract : Objective: We examined the association of outdoor air pollution and meteorological parameters with primary care visits (PCVs) at night due to asthma attack. Setting: A case-crossover study was conducted in a primary care clinic in Himeji City, Japan. Participants: Participants were 1447 children aged 0–14 years who visited the clinic with an asthma attack from April 2010 until March 2013. Exposure: Daily concentrations of air pollutants and meteorological parameters were measured. Primary outcome: PCVs at night due to asthma attack. A conditional logistic regression model was used to estimate ORs of PCVs per unit increment of air pollutants or meteorological parameters (the per-unit increments of particulate matter with an aerodynamic diameter ≤2.5 µm (PM2.5 ) and ozone were 10 μg/m 3 and 10 ppb, respectively). Analyses took into consideration the effects of seasonality. Results: We noted an association between PCVs and daily ozone levels on the day before a PCV (OR=1.17; 95% CI 1.01 to 1.35; p=0.04), as well as between PCVs and 3-day mean ozone levels before a PCV (OR=1.29; 95% CI 1.00 to 1.46; p=0.04), from April until June. We also observed an association between PCVs and daily PM2.5 levels on the day before a PCV from December until March (OR=1.16; 95% CI 1.01 to 1.33; p=0.05). Meteorological parameters, such as hours of sunshine from September until November, atmospheric pressure from April until June, and temperature from April until August, were also found to be associated with PCVs. Conclusions: The findings in the present study supported an association between ozone and PCVs and suggest that certain meteorological items may be associated with PCVs.